Power to regional households: consumer attitudes towards electricity-saving, the solar rebound and the determinants of rooftop solar adoption. Issue 4 (2nd October 2022) - McCarthy, Breda; Liu, Hongbo
ABSTRACT: Solar energy is crucial to the transformation of the energy system, and it is important to promote 'green' energy technologies to achieve the 2015 UN Paris Agreement targets. This study takes a holistic view of consumers' energy-related behaviour by identifying the factors driving the adoption of rooftop solar photovoltaic and by distinguishing the electricity conservation practices of solar and non-solar households. We reveal a nuanced understanding of the rebound effect from a behavioural perspective, which may help solar energy policy formulation and efficient decarbonization pathways in Australia and elsewhere. A face-to-face survey of 325 households in a regional city, principal component analysis and binary probit analysis were used to investigate the intention to install rooftop solar photovoltaic panels. The results show that home ownership, unwillingness to sacrifice personal comforts to save electricity, being pro-energy efficiency, and income are positively related to rooftop solar installation. In addition, different segments, such as the 'energy-efficiency advocate', the 'digital tool lovers' and the 'behaviour change advocates' were identified. Finally, recommendations for policy and practice are made to promote rooftop solar and more careful use of electricity in the residential sector.